Persepsi Komunitas Adat Terpencil Suku Anak Dalam (SAD) terhadap Pelayanan Kesehatan - Mila Triana Sari; Hartati Sandora; Haflin Haflin (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
The solitory custom community of Suku Anak Dalam (SAD) is one of group society whose life are depend to the natural researches in the forest. It is needed an effort to provide service in order to meet their needed, especially health care service for improving their quality of life in the solitary custom Community of Suku Anak Dalam.  This research was conducted in order to know about the persepsion of SAD society towards Health Care Service in the Working Area of Puskesmas Pematang Kabau. This research was conducted on Januari until February 2017 for the purpose of getting understanding about persepsion of solitary custom Community of Suku Anak Dalam towards health care service, the number of participants were 15 people. This is qualitative research with purposive sampling method. The research instruments were indepth interview and interview guide. The result of the research analyzed by using Colaizzi Technique. The finding of the research showed five themes:  the reason of SAD Society in terms of receiving care service. Secondly, the respond of SAD society, thirdly, about the changing and the impact of SAD society. Fourth, the meaning of health care service to SAD society. And fifth the experience of SAD society towards health and service.SAD society gave respond about perception or possitive support towards Health Care Service.